The Effect of Complete Needs Moderation on Time Efficiency, Discounts, Ease of Payment, and Free Shipping in Increasing Repurchase Interest - Sari, Ni Luh Intan; Lestari, Gusti Ayu Putu Dian; Naraswari, Kadek Citra (PT. Global World Scientific, 2023)
This study aimed to determine whether time efficiency, discounts or promotions, easy payments, and free shipping affect purchasing power interest in the TikTok Shop application. The study also examined whether there was a moderating effect between complete needs (moderation factor) on time efficiency (X1), discounts or promotions (X2), easy payments (X3), and free shipping (X4) on purchasing power interest (Y) on TikTok Shop. The sample population was the general Balinese aged 17 to 45 years. In this study, 100 respondents provided assessments through several indicators on a scale of 1 to 5. The method used was the classical assumption test and moderation regression to determine the magnitude of the influence of the moderating relationship between variables M and X (independent). The significance value between variables X and Y before entering variable M showed 0.029, 0.000, 0.016, and 0.005, so the independent factor had a significant positive simultaneous effect on the dependent variable (Y). Meanwhile, when the moderation variable was entered, the significance results were 0.173, 0.001, 0.394, and 0.469, indicating that the complete needs variable (M) could not moderate the time efficiency, easy payment, and free shipping variables on repurchase interest. The complete needs factor was able to moderate discounts or promotions on repurchase interest on TikTok Shop.